Pengaruh Flash Sale dan Sistem Pembayaran Cash on Delivery (COD) terhadap Keputusan Pembelian pada Pengikut Akun Sosial Media TikTok Shopee Indonesia - Kadis, Tasya Salsabila; Siregar, Salim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this study, the focus is on analyzing the influence of Flash Sale and Cash On Delivery (COD) on Purchase Decisions at the Shopee Indonesia marketplace. In carrying out this research the quantitative method was used along with descriptive and verification approaches. Primary data in the form of a questionnaire became a technique in collecting data in this study along with a purposive sampling technique. People who follow Shopee Indonesia social media accounts on the TikTok application make up a population in this study totaling 13.3 million which are then processed using the Isaacs-Michael formula to determine a sample of 384. In the success of this study using the help of SPSS 25 and Microsoft Excel 2019. Keywords: flash sale, cash on delivery (cod), purchase decision.